FACTORS AFFECTING PATIENTS’ DECISION IN SELECTION OF HOSPITAL - Dharmesh, MOTWANI (Strategii Manageriale, 2014)
The study is aimed to identify the factors affecting patients’ decision while selecting hospital. To serve the purpose descriptive research design is used and a structured questionnaire based on ordinal scale is applied to 142 public & 337 private hospital patients. These patients were chosen by stratified purposive sampling method from Udaipur division. The analysis highlighted the four important factors which affects the patients’ decision while selecting the hospital are Qualified & experienced Doctors, 24X7 & Emergency Service, Past Experience with Hospital and Trained Nursing Staff respectively.